Turkey's constraining position on Western reform initiatives in the Middle East - SEVER, AYŞEGÜL (My University, 2007)
Turkey is the Middle East country that has a longest running struggle for democratization with the closest ties with the West via the North Atlantic Treaty Organization, the Council of Europe, and the European Union. Currently, Turkey provides impression of a country preoccupied with crucial internal challenges and ambivalent about its relations with the West. It is a prerequisite for Ankara, advancing its democratic, social, and economic standards in order to assume any role in any regional reform program. Its potential as a security provider will reduce due to uneasy relations with the EU and US. With improve regional circumstance, Turkey could contribute and initiate reform moves in the region by setting a high standard for the democratization of the Middle East by advancement of its own democracy credentials.